2002
DOI: 10.1128/mmbr.66.3.373-395.2002
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction and Regulatory Mechanisms Involved in Control of the σS(RpoS) Subunit of RNA Polymerase

Abstract: SUMMARY The σS (RpoS) subunit of RNA polymerase is the master regulator of the general stress response in Escherichia coli and related bacteria. While rapidly growing cells contain very little σS, exposure to many different stress conditions results in rapid and strong σS induction. Consequently, transcription of numerous σS-dependent genes is activated, many of which encode gene products with stress-protective functions. Multiple signal integration in the control of the cellular σS level is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
791
3
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 851 publications
(826 citation statements)
references
References 240 publications
14
791
3
6
Order By: Relevance
“…These results indicate that salinity and temperature tolerance mechanisms may be coupled at the molecular level, consistent with the findings of previous studies demonstrating that pre-exposure to osmotic stress increased the tolerance to heat stress in V. vulnificus (Rosche et al, 2005). Such coupling may result from temperature and salinity responses using common molecular pathways such as the SOS response pathway, the heat-shock response pathway and the general stress response pathway (Hengge-Aronis, 2002;Diez-Gonzalez and Kuruc, 2009). However, Rosche et al (2005) have demonstrated that the cross-protection between osmolarity and heat in V. vulnificus is independent of rpoS, the master regulator of the general stress response mechanism, and were unable to elucidate the origin of this cross-protection.…”
Section: Discussionsupporting
confidence: 80%
“…These results indicate that salinity and temperature tolerance mechanisms may be coupled at the molecular level, consistent with the findings of previous studies demonstrating that pre-exposure to osmotic stress increased the tolerance to heat stress in V. vulnificus (Rosche et al, 2005). Such coupling may result from temperature and salinity responses using common molecular pathways such as the SOS response pathway, the heat-shock response pathway and the general stress response pathway (Hengge-Aronis, 2002;Diez-Gonzalez and Kuruc, 2009). However, Rosche et al (2005) have demonstrated that the cross-protection between osmolarity and heat in V. vulnificus is independent of rpoS, the master regulator of the general stress response mechanism, and were unable to elucidate the origin of this cross-protection.…”
Section: Discussionsupporting
confidence: 80%
“…There are more than 70 genes in the RpoS regulon, and most of them encode proteins that help the cell survive the insults encountered by non-growing cells. Thus, RpoS is considered to be a master regulator of a general stress response (reviewed in [17]). …”
Section: The General Stress Responsementioning
confidence: 99%
“…One of these is the alternative sigma factor s 38 (RpoS), which plays a key role in the survival of bacteria during starvation or exposure to stress conditions and is required for the expression of many genes in the stationary growth phase (virulence factors and secondary metabolites). It may not, however, be essential for cell viability (Hengge-Aronis, 2002;Schuster et al, 2004;Venturi, 2003). A second pathway involves the intervention of the GacS/GacA TCS in the QS cascade.…”
Section: Introductionmentioning
confidence: 99%